A Unified Treatment of Horizontal Direct Investment, Vertical Direct Investment, and the Pattern of Trade in Goods and Services. - Markusen, J; Venables, A; Konan, D; Zhang, K (National Bureau of Economic Research, 1996)
This paper contributes to research endogenizing multinational firms in general-equilibrium trade models. We attempt to integrate separate contributions on horizontal multinationals which produce the same final product in multiple locations, with work on vertical multinationals, which geographically fragment production by stages. Previously derived results now emerge as special cases of a more general model. Vertical multinationals dominate when countries are very different in relative factor endowments. Horizontal multinationals dominate when the countries are similar in size and in relative endowments, and trade costs are moderate to high. In some cases, foreign investment or trade liberalization leads to a reversal in the direction of trade. Investment liberalization can also lead to an increase in the volume of trade and produces a strong tendency toward factor-price equalization. Thus direct investment can be a complement to trade in both a volume-of-trade sense and in a welfare sense.